Evidence of reduced interface states in Al2O3/AlGaN MIS structures via insertion of ex situ regrown AlGaN layer. (22nd September 2022) - Baratov, Ali; Kawabata, Shinsaku; Urano, Shun; Nagase, Itsuki; Ishiguro, Masaki; Maeda, Shogo; Igarashi, Takahiro; Nezu, Toi; Yatabe, Zenji; Matys, Maciej; Kachi, Tetsu; Adamowicz, Boguslawa; et al.
Abstract: We report on the impact of the 3 nm thick ex situ AlGaN regrown layer prior to insulator deposition on the interfacial properties of Al2 O3 /AlGaN/GaN metal–insulator–semiconductor (MIS) structures. MIS-capacitors (MIScaps) with regrown AlGaN layer exhibited anomalously excessive threshold voltage shift compared to reference sample without regrown AlGaN, suggesting highly reduced interface states density ( D it ). Moreover, MIScaps with regrown AlGaN layer exhibited "spill-over" in the capacitance–voltage profiles, further evidencing the improved Al2 O3 /AlGaN interfaces. Fabricated three-terminal MIS-HEMTs with regrown AlGaN showed less hysteresis in transfer curves, enhanced maximum drain current, and increased linearity over the reference device.